KEPUASAN LAYANAN IBU HAMIL PENGGUNA PROGRAM BPJS DI PUSKESMAS SE-KOTA BENGKULU TAHUN 2014 - Rachmawati, Rachmawati (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
With the implementation of BPJS’S programs that replace Jampersal, then patientsatisfaction from cost faktors or foundation complete. Patient Satisfaction can be also assessedfrom the age of mother, education, employment and maternal parity use BPJS’S program. Thepurpose of this observation is for description the level of mother’s satisfaction towardimplementation of BPJS’S program in all clinic of Bengkulu city. The design that use is crossecsional with all of population pregnant mother that do examination in all clinic of Bengkulucity amount 115 people’s taken with Accidental sampling technic. Level analysis of satisfactionof pregnant mother toward implementation of BPJS based on the comparison of the distributionthe patient satisfaction that look from age, education, employment and parity also statistikanalysis with Chi Square test. The result of observation was not relation between age, education,employment of pregnant mother toward implementation BPJS’S program in all clinic ofBengkulu city, while parity analysis there is relation of maternal parity toward implementationBPJS’S program in all clinic Bengkulu city. Be expected medical employment can be improveimplementation BPJS’S program start from level of primer until the level of sekunder be betterthan before.